Circular & sustainable adaptive reuse of fragile industrial heritage sites. Regenerating Ex SITOCO - Serena Baiani; Paola Altamura (Techne, 2025)
In the fluid design boundaries of technological culture engaging with heritage-urban mine, resilient resource-the research explores innovative experimentation in disused industrial sites in fragile areas. Through environmental design and a lifecycle perspective, it proposes balanced landscape integrations aligned with evolving social, economic, and environmental needs, while addressing multiple risks. The research prioritises control actions on biophysical and morphological components, adopting a circular regeneration approach to reduce the embodied and operational energy of buildings, activating passive functioning to support an “ecologically resilient” transition. The operational, replicable, multi-scale methodology was tested in various pilot cases, exemplified in this paper by the Ex SITOCO site in the Orbetello lagoon.